(3JfXje GdeTQhYGJ GdUZjQIs - (3MeOj(B, (3GdMfGhjs ((3GdGScfOQjI(B:s (3eQcR GdGScfOQjI ddcJGH(B,s, 2006)
(3GdJacjQ aj GbGeI GdeTQhY h OQGSI GdLOhi , HYV GdeaGgje GdGSGSjI Mhd GdfTGW GdGbJUGOj , GdJfejI GdGbJUGOjI , GdbWGYGJ GdGbJUGOjI (B...(3, GOGQI GdeTQhY hhUGjG h NHQGJ GVGajI Mhd GdeTQhYGJ GdQjajI h GUdGM GdGQGVj (B...(3, aQU hebheGJ GdfLGM (B.s
Keywords: (3GdJfXjes; (3GdeTGQjYs